Perlakuan Akuntansi Aset Tetap Berdasarkan SAK ETAP Pada PT Asia Pacific Energindo Di Jakarta - Pratiwi Nila Sari (Jurnal Kajian Ilmiah, 2020)
This study aims to analyze the accounting treatment of fixed assets for recognition, measurement, depreciation, termination, and presentation and disclosure at PT. Asia Pacific Energindo on the list of fixed assets in 2017. Tests are carried out by analyzing the extent to which the company has implemented a fixed asset accounting policy based on the Entity Financial Accounting Standards without Public Accountability (SAK ETAP) Chapter 15 in the company's operational activities. This study uses a qualitative descriptive analysis method that is to thoroughly describe the fixed asset accounting policies applied to PT. Asia Pacific Energindo in Jakarta and compared to SAK ETAP Chapter 15. The results of this study indicate that the recognition, measurement, depreciation, termination, and presentation and disclosure of fixed assets in practice are in accordance with the Entity Financial Accounting Standards without Public Accountability (SAK ETAP). Depreciation method uses a straight-line method, fixed assets are discontinued or released from usage then the book value is calculated and then all accounts related to the asset are written off. The presentation of accumulated depreciation is carried out separately for all fixed assets so that it can be seen directly how much accumulated depreciation for each group of fixed assets. This treatment makes it easier to read financial statements. For those who need financial statements, it will be easy to know some of the accumulated amount of the fixed assets in question and the book value of each of the asset groups. Keywords: Accounting, Fixed Assets, SAK ETAP chapter 15 Abstrak Penelitian ini bertujuan untuk menganalisis perlakuan akuntansi aset tetap atas pengakuan, pengukuran, penyusutan, penghentian dan penyajian serta pengungkapan pada PT. Asia Pacific Energindo pada daftar aset tetap tahun 2017. Pengujian dilakukan dengan menganalisis sejauh mana perusahaan telah menerapkan kebijakan akuntansi aset tetap berdasarkan Standar Akuntansi Keuangan Entitas Tanpa Akuntanbilitas Publik (SAK ETAP) Bab 15 dalam aktivitas operasional perusahaan. Penelitian ini menggunakan metode analisis deskriptif kualitatif yaitu menjabarkan secara menyeluruh terhadap kebijakan akuntansi aset tetap yang diterapkan pada PT. Asia Pacific Energindo di Jakarta dan dibandingkan dengan SAK ETAP Bab 15. Hasil penelitian ini menunjukan bahwa pengakuan, pengukuran, penyusutan, penghentian dan penyajian serta pengungkapan aset tetap dalam prakteknya sudah sesuai dengan Standar Akuntansi Keuangan Entitas Tanpa Akuntanbilitas Publik (SAK ETAP). Metode penyusutan menggunakan metode garis lurus, aset tetap dihentikan atau dilepaskan dari pemakaian maka dihitung nilai bukunya untuk kemudian semua akun yang berhubungan dengan aset tersebut dihapuskan. Penyajian akumulasi penyusutannya dilakukan secara terpisah atas seluruh aset tetap, sehingga dapat dilihat langsung berapa akumulasi penyusutan untuk masing-masing kelompok aset tetap. Perlakuan seperti ini mempermudah membaca laporan keuangan. Bagi yang membutuhkan laporan keuangan, akan mudah mengetahui beberapa jumlah akumulasi terhadap aset tetap yang bersangkutan dan nilai buku dari masing-masing kelompok aset tersebut. Kata kunci: Akuntansi, Aset Tetap, SAK ETAP Bab 15